Optimizing Teacher Productivity: The Impact of Work Discipline and Compensation - Kartiko, Ari; Ma’arif, Muhammad Anas; Sirojuddin, Akhmad; Zamroni, Afif; Nurihidin, Edi (JURNAL AL-TANZIM, 2024)
This research aims to explore teacher productivity which is influenced by work discipline variables and the compensation received by teachers. The question asked in this research is how work discipline and compensation influence teacher productivity partially or simultaneously. Second, which variable has the dominant influence on teacher productivity? The method used in this research is qualitative research with a causality approach or cause and effect resulting between the variables being measured. The data collection technique used a questionnaire obtained from 39 teacher respondents at the Ma'Arif Nahdlatul Ulama Talang Prigen Foundation, Pasuruan. The data obtained was subjected to classical assumption tests, as well as hypothesis tests, partial tests and simultaneous tests. The results obtained are that work discipline and compensation have a dominant influence on teacher work productivity, but compensation has a more dominant influence as reflected in the compensation indicator which has a fairness value, making teacher motivation increase and also adequate compensation will increase the attractiveness of talents. new people who want to serve in the institution.